2008
DOI: 10.1590/s0103-64402008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nystatin, fluconazole and propolis on poly(methyl methacrylate) resin surface

Abstract: The prevalence of candidosis in denture wearers is as well established as its treatment with antifungal agents (AAs). However, little research has been done regarding the effects of AAs on denture base surfaces. Therefore, the aim of this study was to evaluate the effects of fluconazole (FLU), nystatin (NYS) and propolis orabase gel (PRO) on poly (methyl-methacrylate) (PMMA) surfaces. Deionized water and orabase gel without any active component were used as control groups. Conventional heat-polymerized (Clássi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
(36 reference statements)
2
19
0
2
Order By: Relevance
“…Silva et al evaluated the effects of 10% EEP on acrylic resin surfaces, and reported an increase in the hardness of resin accumulating on the surface. They proposed that this could act as a barrier for adhesion of Candida species (7).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Silva et al evaluated the effects of 10% EEP on acrylic resin surfaces, and reported an increase in the hardness of resin accumulating on the surface. They proposed that this could act as a barrier for adhesion of Candida species (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the most commonly used concentration of propolis (10% EEP) was selected for testing (7,25,26), and its effectiveness was found to be limited when compared to the other chemical disinfectants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations